التوزيع الأمثل للقوى العاملة على القطاعات الاقتصاديّة في سورية خلال الفترة الزمنيّة 1995-2010 باستخدام أسلوب البرمجة الخطيّة - الرفاعي عبد الهادي; اسماعيل عصام; حبيب غدير (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف هذا البحث إلى إيجاد النموذج الأمثل لتوزيع القوى العاملة على القطاعات الاقتصاديّة في سورية خلال الفترة 1995-2010 باستخدام أسلوب البرمجة الخطيّة, وذلك من خلال تسليط الضوء على تغيّر حجم القوة البشريّة بشكل عام, والذي يعاني من خلل في تركيبه من الناحية القطاعيّة أو الديموغرافيّة, الأمر الذي أثّر سلباً على تركيبة القوى العاملة بحسب القطاعات, ممّا أدّى إلى زيادة في عدد السكان الذين هم خارج القوى العاملة عبر الزّمن, وقد انتهى البحث إلى النتائج الآتية: - تزداد أعداد السكّان خارج القوى العاملة بشكل مستمرّ عبر الزّمن, وكان للتفرّغ للعمل المنزلي الأثر الأكبر في هذه الزيادة. - تبيّن إمكانيّة بناء نموذج أمثل لتوزّع القوى العاملة على القطاعات في حالتي عدم الأخذ بالحسبان لعدد العاطلين عن العمل والأخذ بعدد العاطلين عن العمل. - تبيّن أنّ الإنتاجية الكليّة عند إيجاد التوزيع الأمثل للقوى العاملة كانت أكبر منها في حالة التوزّع الفعلي للقوى العاملة, كما أنّ الأخذ بعدد العاطلين عن العمل عند توزيع القوى العاملة على القطاعات أدّى إلى زيادة في الإنتاجية عن الحالة التي لم تأخذ عدد العاطلين عن العمل بالحسبان. This research aims to find the optimal model for the distribution of manpower to economic sectors within the period 1995-2010 by using linear programming. This will be done by highlighting the changes in the size of human resources in general, which suffers from a malfunction in its sectoral and demographic structure. This malfunction negatively affected manpower sectoral structure, which caused an increase in the population off manpower along time. Finally, the research yielded the following results: - Numbers of people off manpower are increasing consequently along time, as a result of full-time house commitment. - It is possible to build the optimal model for the distribution of manpower in case we don’t take into consideration the numbers of the unemployed and in case we take into consideration the numbers of the unemployed. - Total productivity in the case of optimal distribution of manpower is larger than total productivity in case of the actual distribution. In addition, taking into consideration the numbers of the unemployed at manpower distribution to sectors led to an increase in the total productivity compared to the case in which the numbers of the unemployed were not taken into consideration.